Migration: The Bahamas and the Caribbean: A Selective Bibliography - Swann, Christine E. (International Journal of Bahamian Studies, 2014)
Migration is a topic of great importance to the people of The Bahamas and indeed of the entire Caribbean region. We in the region have had a rich history of immigration and emigration and even today this trend continues although there have been marked changes over the years. It would be virtually impossible to include absolutely everything on the subject of migration in the Caribbean region, but this effort serves as a selective listing of some of the most relevant and useful resources on the topic.